Secularism between its conditions of Correctness and Civilized Effects - طوبال علي, علي; ابراهيم رزوق; فارس النداف (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Secularism is a cultural value produced by civilizational development. It is based on separating religion from the state and the state's neutrality towards various religions and ethnicities within society. Secularism encountered a relatively long historical process through which the importance of secularism was firmed—though misunderstood and attacked by some conservative groups-- being a viable solution to many problems that arose from the use of religion in politics. The application of secularism in managing the affairs of societies and states was positively reflected on the reality of human life and development in those states. Adopting secularism in its correct form, which is necessarily identical with democracy and based on the principle of equal opportunities in managing the affaires of societies, helps to achieve an optimal use of human abilities and natural recourses, elevates human thought and the values of society, helps dispel illusions and myths and opens broad horizons for humanized development and civilizational advancement.